Assessing Constitutional Court Independence After Controversial Rulings in Political Arena - Mokh. Thoif; Tutik Asmorowati (CV. AFDIFAL MAJU BERKAH, 2026)
This study investigates how judicial independence is discursively constructed and contested following controversial rulings by Indonesia’s Constitutional Court. Drawing on theories of legal realism, neo-institutionalism, and discourse analysis, the research explores whether formal guarantees of judicial autonomy hold symbolic weight amid growing perceptions of political alignment. Using a qualitative case study approach, data were collected through semi-structured interviews with legal scholars, civil society actors, and journalists, complemented by discourse analysis of court rulings and media texts. Findings reveal that the Court’s independence is widely framed as situational, with legitimacy perceived to fluctuate based on alignment with dominant political interests. Respondents highlighted themes of strategic judicial reasoning, media-driven delegitimization, and performative institutional responses, suggesting that public trust is shaped less by institutional design and more by narrative coherence and interpretive transparency. Rather than neutral arbiters, courts are increasingly viewed as political actors embedded within broader struggles for power. The study contributes to literature on judicial politicization and democratic resilience by emphasizing the role of discourse in shaping perceptions of legality and legitimacy. It also offers practical insights for reform, including the need for transparent appointments and greater communicative accountability. The findings suggest that in hybrid regimes, judicial independence must be understood not only as a structural condition but as an ongoing, contested performance shaped by elite discourse, public critique, and symbolic legitimacy.